1999
DOI: 10.1093/nar/27.10.2063
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sequence analysis of tmRNA

Abstract: Minimal secondary structures of the bacterial and plastid tmRNAs were derived by comparative analyses of 50 aligned tmRNA sequences. The structures include 12 helices and four pseudoknots and are refinements of earlier versions, but include only those base pairs for which there is comparative evidence. Described are the conserved and variable features of the tmRNAs from a wide phylogenetic spectrum, the structural properties specific to the bacterial subgroups and preliminary 3-dimensional models from the pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 44 publications
5
78
1
Order By: Relevance
“…tmRNA: The structure of tmRNA contains four H-type pseudoknots and is roughly globular [47]. The consensus structure predicted by our program is based on the alignment of 8 bacterial tmRNA sequences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…tmRNA: The structure of tmRNA contains four H-type pseudoknots and is roughly globular [47]. The consensus structure predicted by our program is based on the alignment of 8 bacterial tmRNA sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative sequence analysis revealed conserved pseudoknots e.g. in rRNAs [6], RNase P RNAs [5,18], and tmRNA [47].…”
Section: Introductionmentioning
confidence: 99%
“…The extensive structural variation in diverse tmRNA sequences, and the sporadic occurrence of some helical regions, has been noted previously (Williams & Bartel 1998;Zwieb et al+, 1999)+ Extensive structural variability occurs even within the gamma-group proteobacterial sequences reported here, confirming the notion that much of the tmRNA structure can vary with little effect on its basic function+ Indeed, experimental modifications of the E. coli tmRNA have shown that three of the pseudoknots (pk2, pk3, and pk4; Fig+ 4) are completely interchangeable and can even be replaced by unstructured regions with no significant loss of function (Nameki et al+, 2000)+ We suspect that these phylogenetically volatile regions of the structure occur on the surface of the functional unit because of spacefilling constraints (Burgin et al+, 1990), whereas conserved structural elements and sequences are expected to form the functional core of tmRNA+ A recent crosslinking study also may shed some light on the variability of tmRNA across different lineages+ In this study, the investigators discovered substantial crosslinking between tmRNA and ribosomal protein S1 (Wower et al+, 2000)+ Ribosomal protein S1, however, is not found in all bacterial lineages, specifically the Low GϩC group of Gram-positive bacteria+ Thus, at least in this group of Bacteria, tmRNA must find an alternative binding site+ If the binding site of tmRNA can change radically, as this study suggests, then such extensive variability in tmRNA secondary structure may be expected+…”
Section: Discussionmentioning
confidence: 63%
“…The new tmRNA sequences were first aligned to the known gamma-proteobacterial sequences using Clustal W (Aiyar, 2000) leaving the original alignment unchanged+ We then added the natural community sequences to 87 other tmRNA sequences collected from the internet (Knudsen et al+, 2001) and manually refined the alignment by keying on elements of structure using the ARB Program (Strunk & Ludwig, 1999)+ The basic proposed tmRNA secondary structure model was used as a template to align homologous regions (Williams & Bartel, 1996;Zwieb et al+, 1999)+ All of the comparative analyses were based on multiple alignments that included only the positions that were homologous to the E. coli nucleotides+ Other sections of the alignments contained numerous gaps and were not considered reliable+ To predict tmRNA structure, we calculated the phylogenetically based R ij and H ij statistics for the data set using the, appropriately titled, Rij and Hij programs compiled on a PC running Slackware Linux version 3+5 + These statistics incorporate information from the phylogenetic relationships among the sequences and have been shown to be more accurate than standard mutual information methods (Akmaev et al+, 1999+ The phylogenetic tree for the 107-sequence tmRNA data set used in the statistical analysis was calculated using the neighbor-joining algorithm in the PHYLIP phylogeny package (Felsenstein, 1993)+ For given pairs of positions, the R ij and H ij statistics compare the rates of evolution of each position independently (calculated as the independent likelihood) to the joint rates of evolution (joint likelihood) of the two positions+ If the independent rate of evolution for two positions is very high (low independent likelihoods) but the positions always change together (high joint likelihood) then the values for these statistics will be high+ Both statistics calculate the independent likelihoods using the phylogenetic tree, but only H ij utilizes the phylogenetic tree to calculate the joint likelihoods, making this statistic much slower to calculate+ However, the H ij statistic approximates a x 2 distribution with nine degrees of freedom, allowing for an assessment of confidence in particular proposed pairings+ In the course of the analysis, we utilized the computationally faster R ij method to identify the set of initial pairs with high correlation values and then used the computationally intensive H ij statistic to determine which of these pairs were statistically significant+ We also performed mutual information (MI) analyses using the in-house ALEX program (version 1+0) designed by Dan Frank, which calculated MI values based on previous work (Gutell et al+, 1992)+…”
Section: Alignment and Comparative Analysesmentioning
confidence: 99%
See 1 more Smart Citation